2017
DOI: 10.1021/acs.jchemed.7b00413
|View full text |Cite
|
Sign up to set email alerts
|

Musical Example To Visualize Abstract Quantum Mechanical Ideas

Abstract: Quantum mechanics is a notoriously difficult subject to learn, due to a lack of real-world analogies that might help provide an intuitive grasp of the underlying ideas. Discrete energy levels and absorption and emission wavelengths in atoms are sometimes described as uniquely quantum phenomena, but are actually general to spatially confined waves of any sort. Here, we provide an experiment demonstrating the acoustic spectroscopy of a drum. We show that a struck drum emits sounds of discrete frequencies (tones)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…Os conceitos de orbital atômico estão relacionados à elaboração teórica das estruturas de átomos, moléculas e cristais, de modo que, são fundamentais para a compreensão e a explicação de grande parte da Química. Entretanto, a literatura mostra que estudantes de Química ao redor do mundo (Bianco & Meloni, 2019;Cataldo, Griffith & Fogarty, 2018;Eagle, Seaney & Grubb, 2017;Ligouri, 2014;Saputra et al, 2015) assim como licenciandos em formação inicial (Türk & Tüzün, 2018) encontram dificuldades na apropriação dos conceitos ligados à Teoria Quântica e, de modo específico, dos conceitos de orbital.…”
Section: Introductionunclassified
“…Os conceitos de orbital atômico estão relacionados à elaboração teórica das estruturas de átomos, moléculas e cristais, de modo que, são fundamentais para a compreensão e a explicação de grande parte da Química. Entretanto, a literatura mostra que estudantes de Química ao redor do mundo (Bianco & Meloni, 2019;Cataldo, Griffith & Fogarty, 2018;Eagle, Seaney & Grubb, 2017;Ligouri, 2014;Saputra et al, 2015) assim como licenciandos em formação inicial (Türk & Tüzün, 2018) encontram dificuldades na apropriação dos conceitos ligados à Teoria Quântica e, de modo específico, dos conceitos de orbital.…”
Section: Introductionunclassified
“…52 There are few realworld macroscopically observable demonstrations of quantum mechanical ideas. 31 Nevertheless, from the pedagogical practice research made regarding the use of analogies, it was possible to confirm that we can prevent students' misinterpretations and the formation of misconceptions. Using analogies for which analogs were familiar and interesting to students and to a systematic presentation model of analogies, such as the FAR Guide, which involves a prelesson planning and a discussion of where the analogy breaks down, promoted successful student learning of the quantum model of the atom.…”
Section: Interviewer: But Did You Know What An Atom Is?mentioning
confidence: 93%
“…Obviously, care must be taken in presenting them to students to avoid misinterpretations and the formation of misconceptions. Over the years, the literature has been presenting analogies about the atom and its quantum atomic model. , Nevertheless, different analogies are needed because students continue to display unscientific mental models about the atom . Indeed, there is a lack of good analogies for this subject matter …”
Section: Students’ Difficulties Regarding the Atom Concept And The Qu...mentioning
confidence: 99%
See 1 more Smart Citation
“…Physical chemistry is traditionally perceived by students as a difficult subject to learn, which leads to low expectations regarding success and negative perceptions of the course. , For example, understanding chemical bonding and the use of infrared (IR) spectroscopy to determine the structure of a molecule can be challenging because of the abstract nature of the subject. A study by Sözbilir in 2004 demonstrated that more than half of students perceive the chemical concepts in physical chemistry to be abstract and difficult to grasp .…”
Section: Introductionmentioning
confidence: 99%